2018
DOI: 10.1186/s13229-018-0240-6
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal administration of exosomes derived from mesenchymal stem cells ameliorates autistic-like behaviors of BTBR mice

Abstract: Autism spectrum disorders (ASD) are neurodevelopmental disorders characterized by three core symptoms that include social interaction deficits, cognitive inflexibility, and communication disorders. They have been steadily increasing in children over the past several years, with no effective treatment. BTBR T+tf/J (BTBR) mice are an accepted model of evaluating autistic-like behaviors as they present all core symptoms of ASD. We have previously shown that transplantation of human bone marrow mesenchymal stem ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
139
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 137 publications
(146 citation statements)
references
References 50 publications
4
139
1
2
Order By: Relevance
“…Indeed, using the same BTBR model, we were able to show that intranasal administration of human MSCs derived exosomes (MSC-exo) resulted in significant improvement in the core symptoms including social interaction, ultrasonic communication, and repetitive behaviors 13 . Furthermore, we have demonstrated that MSC-derived exosomes migrate to specific neuropathological locations in rodent models for stroke, Parkinson's Disease Alzheimer's Disease, spinal cord injury and ASD.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…Indeed, using the same BTBR model, we were able to show that intranasal administration of human MSCs derived exosomes (MSC-exo) resulted in significant improvement in the core symptoms including social interaction, ultrasonic communication, and repetitive behaviors 13 . Furthermore, we have demonstrated that MSC-derived exosomes migrate to specific neuropathological locations in rodent models for stroke, Parkinson's Disease Alzheimer's Disease, spinal cord injury and ASD.…”
Section: Introductionmentioning
confidence: 93%
“…Reciprocal dyadic social interaction test. The reciprocal dyadic social interaction test was done as previously described [32][33][34] . Prior to the test, each mouse was separated for social isolation of 1-2 hours.…”
Section: Behavioral Testsmentioning
confidence: 99%
See 3 more Smart Citations